Traditional Use of Natural Resources of Local Old Believer (Semeiski) communities of Transbaikalia in the 18th—20th Centuries: Theoretical and Methodological Basis of the Study - S. A. Kozlova (Научный диалог, 2020)
Some theoretical aspects of the study of the traditional nature management of local Old Believer (Semei) communities living in Transbaikalia are considered. On the basis of the available theoretical works of cultural geography, ethnology, cultural studies, sociology and other related disciplines, the analysis of the concepts of “local community”, “life support”, “traditional nature management” in relation to Old Believer communities has been carried out. An attempt has been made to identify the merits of studying the Old Believers in Transbaikalia using the category of the local community. It is shown that in a comprehensive study of local communities of the Semeiskaya Transbaikalia, the following elements emerge: nature as the life environment of Old Believer communities, natural resources, traditions and a set of actions that regulate social and industrial life, the religious basis that determines the behavior of the community and its individual members, the main material and spiritual needs, to the satisfaction of which most of the energy of human collectives is directed. It is noted that the concept of “life support” is diverse, dynamic and has wide adaptive capabilities. The category of traditional nature management is used to study the cultural and geographical continuity of the Semeiskys and the specifics of their life support in the conditions of the Trans-Baikal geographic environment. In this regard, the traditional use of natural resources of Semeiskiye is presented as a set of strategies for the rational use of natural and land resources.